Method for deproteinization of chitosan (2003)
Methods for deproteinizing chitosan are provided. Proteins are dissolved in aqueous solution under intensive agitation. Precipitated agglomerated microcrystalline product Is subject to aqueous acidic or basic salt solution, from which dissolved proteins can be removed. Residual product is deproteinized chitosan.